INTEREST RATE SHOCKS AND HOUSEHOLD CONSUMPTION PATTERNS - Munivenkatappa K (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Interest rate shocks, characterized by sudden and unexpected changes in benchmark interest rates, play a critical role in shaping household consumption patterns, particularly in emerging economies like India. These shocks, often driven by monetary policy adjustments from central banks such as the Reserve Bank of India (RBI), influence the cost of borrowing, savings behavior, and overall consumer confidence. Understanding how these shocks affect household consumption is vital for policymakers aiming to manage economic growth, inflation, and financial stability. This paper examines the complex relationship between interest rate shocks and household consumption patterns in the Indian context. The analysis highlights that while interest rate changes directly impact the affordability of credit for households, the degree of this impact varies across different income groups, geographic regions, and types of consumption. Urban households with greater access to formal credit markets tend to respond more strongly to interest rate fluctuations, particularly in their discretionary spending on durable goods, automobiles, and housing. In contrast, rural households and lower-income groups, often reliant on informal credit channels, exhibit a weaker and more delayed response. The study also emphasizes the role of structural factors such as financial inclusion, digital lending, consumer expectations, and credit availability in mediating the transmission of interest rate shocks to consumption. Case studies from India, especially during the 2018-2022 period marked by significant monetary policy shifts, reveal that while lower interest rates stimulated certain sectors like real estate and automobile sales, broader consumption patterns were also shaped by factors such as income security, employment conditions, and inflationary pressures. In conclusion, the relationship between interest rate shocks and household consumption in India is multifaceted and asymmetric. Effective policy interventions must consider these structural nuances to ensure that monetary policy adjustments translate into sustainable and inclusive consumption growth across all segments of society.